Phương pháp chiếu lặp giải phương trình tích phân kì dị với nhân Hilbert trong không gian L2 - Quảng, Lê Xuân (Journal of Computer Science and Cybernetics, 2016)
In this paper the iterative-projection method is used for solving the singular integral equation with the Hilbert kernel. The method is convergent with the rate of power.